Highly prospective objects of the mineral and raw material base of Ukraine. Part 1. Metallic minerals - Mykhailov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A short description of the highly promising mineral and raw material base of metallic minerals of Ukraine is provided. It includes the following deposits and occurrences: complex carbonatite rare metal-apatite Novopoltavske deposit (REE, Nb, Ta, P2O5); complex zirconium-rare-earth-niobium Mazurivske (Oktyabrske) deposit (REE, Zr, Nb); complex rare earth-zirconium Azovske deposit (REE, Zr); Anadolske rare earth deposit (REE); rare earth occurrences Petrovo-Hnutivske (RZE) and Balka Korabelna (RZE); placer complex ilmenite-zirconium deposits Malyshevske (Ti, Zr) and Tarasivske (Ti, Zr); indigenous complex rare-earth-zirconium Yastrubetske deposit (REE, Zr); Shevchenkivske deposit of spodumene ores (Li); Polokhivske deposit of petalite ores (Li); Stankuvatske deposit of spodumene-petalite ores (Li); manifestation of Kruta Balka (Li); Zhovtorichenske complex iron-uranium-vanadium-scandium deposit (Sc, Fe, U, V); coal of the Donetsk basin (Ge). Among the metallic minerals of Ukraine, these deposits have the highest level of investment attractiveness, the lowest investment risks, are characterized by an average level of competition and can be recommended as priority objects for investment in their study and industrial development. To determine the investment prospects of specific objects, a preliminary geological and economic assessment of the feasibility and profitability of their industrial development is necessary.
Keywords: mineral base; deposit; strategic minerals; investment attractiveness